Agronomic traits associated with genetic gains in maize yield during three breeding eras in West Africa - Badu-Apraku, Baffour; Fakorede, M.A.B.; Oyekunle, M. (2014)
Studies on genetic gains in grain yield in maize (Zea mays L) is crucial to identify traits of potential value and the necessary modifications in breeding methodologies and strategies for increased progress in future breeding ef-forts. Fifty early-maturing maize cultivars developed during three breeding eras were evaluated for 2 yr in two field experiments involving 16 multiple stress (drought, Striga-infested, and low soil nitrogen) environments and 35 optimum environments to determine the changes in agronomic traits associated with the genetic gains in grain yield over three breeding eras. The average rate of increase in grain yield was 30 kg ha–1 yr-1 corresponding to 1.59% annual genetic gain across multiple stresses. Among the agronomic traits under stress, only ears per plant (0.32% year-1), ear aspect (-0.51% year-1), plant aspect (-0.24% year-1) and days to anthesis (0.11% year-1) changed significantly (P<0.05 or <0.01) during the three eras. The increase in grain yield from the first to the third generation cultivars across stress environments was associated with significant improvements in plant and ear aspects, increased ears per plant and stay green characteristic. Under optimal growing environments, the increase in grain yield from the first to the third generation cultivars was 1.24% per annum and the gain was associated with significant improvements in plant and ear heights, plant and ear aspects, husk cover, and increased ears per plant. The results indicated that substantial progress has been made in breeding for cultivars with combined tolerance/resistance to the three stresses during the past 22 years.